Diversity and Composition of Demersal Fishes along a Depth Gradient Assessed by Baited Remote Underwater Stereo-Video - Zintzen, V.; Anderson, M.; Roberts, C.; Harvey, Euan; Stewart, A.; Struthers, C. (Public Library of Science, 2012)
Background: Continental slopes are among the steepest environmental gradients on earth. However, they still lack finer quantification and characterisation of their faunal diversity patterns for many parts of the world.Methodology/Principal Findings: Changes in fish community structure and diversity along a depth gradient from 50 to 1200 m were studied from replicated stereo baited remote underwater video deployments within each of seven depth zones at three locations in north-eastern New Zealand. Strong, but gradual turnover in the identities of species and community structure was observed with increasing depth. Species richness peaked in shallow depths, followed by a decrease beyond 100 m to a stable average value from 700 to 1200 m. Evenness increased to 700 m depth, followed by a decrease to 1200 m. Average taxonomic distinctness ?+ response was unimodal with a peak at 300 m. The variation in taxonomic distinctness ?+ first decreased sharply from 50 to 300 m, then increased beyond 500 m depth, indicating that species from deep samples belonged to more distant taxonomic groups than those from shallow samples. Fishes with northern distributions progressively decreased in their proportional representation with depth whereas those with widespread distributions increased.Conclusions/Significance:This study provides the first characterization of diversity patterns for bait-attracted fish species on continental slopes in New Zealand and is an imperative primary step towards development of explanatory and predictive ecological models, as well as being fundamental for the implementation of efficient management and conservation strategies for fishery resources.